Implementasi Green Economy pada Sistem Instalasi Pengolahan Air Limbah Tahu dan Sensor Terintegrasi di Kediri - Srikalimah; Rizky Arief Shobirin; Yanu Shalahuddin; Muhammad Syahrul Mubarok; Aqli Supremadi Naufal Pinandhita (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2022)
Every industry has special attention to environmental preservation; however, it has become an unresolved problem in the industrial center of tofu village. Based on the analysis, there were problems related to liquid waste produced by tofu craftsmen that doesn’t meet the Quality Standards for liquid waste of the Food Products Industry, limited costs, land, and space thus that it didn’t meet the adequacy of space for Wastewater Treatment Plants (WWTP). The PKM (Community Service Program) activity aimed to implement Green Economy Concept on Integrated WWTP Systems and Sensors for the Kediri Tofu Industry as an effort to solve the waste problem in the tofu industry. This activity began with field observations, compatibility and requirements analysis, construction design and designing WWTP systems and sensors, small-scale trials, analysis, and evaluation. The WWTP system used involves components of pre-treatment, neutralization, coagulation and flotation, sedimentation, and filtration. The designed sensors included Arduino Nano-based pH meter and TDS meter sensors that were connected to computers and smartphones by Arduino IDE and Blynk software. It was hoped that this activity might spur business actors to actively participate in solving waste problems and reducing environmental impact pollution with all the space and cost limitations.